Identification of business performance scenarios by productivity, profitability and competitiveness according to the Morphol model: Case of a business sample. - CHABI , Tayeb (Dirassat Journal Economic Issue, 2015)
The purpose of this empirical research is to identify the key scenarios for achieving performance in a business. The study is carried out on a sample of companies in the Soummam region. To conduct our study, we developed a questionnaire to formulate a field of hypotheses and their evaluations by the companies surveyed, then a useful field of responses is produced according to the "Morphol" GODET model. M, (2001). The results of our survey allowed the construction of a system of variables and indicators, the visualization of the results on graphs and proximity plans and then proceeded to their analysis and the identification of the key performance scenarios in the companies surveyed.